Correction for specimen movement and rotation errors for in-vivo Optical Projection Tomography - Birk, Udo J.; Rieckher, Matthias; Konstantinides, Nikos; Darrell, Alex; Sarasa-Renedo, Ana; Meyer, Heiko; Tavernarakis, Nektarios; Ripoll Lorenzo, Jorge (Biomedical optics express, 2010)
The application of optical projection tomography to in-vivo experiments is limited by specimen movement during the acquisition. We present a set of mathematical correction methods applied to the acquired data stacks to correct for movement in both directions of the image plane. These methods have been applied to correct experimental data taken from in-vivo optical projection tomography experiments in Caenorhabditis elegans. Successful reconstructions for both fluorescence and white light (absorption) measurements are shown. Since no difference between movement of the animal and movement of the rotation axis is made, this approach at the same time removes artifacts due to mechanical drifts and errors in the assumed center of rotation.
Gesehen am 06.02.2023